Kontradiksi Hak Komunal dan Hak Ulayat dalam Hukum Pertanahan Indonesia: Tinjauan Yurisprudensi dan Regulasi Indonesia - Tandori, Tandori; Supriyanto, V. Hari (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2025)
This research analyzes the juridical dialectic between customary law (hukum adat) and national land law in Indonesia, examining the contradictions in the Supreme Court's jurisprudence on customary land rights (hak ulayat) and the conceptual shift towards communal rights (hak komunal) in legislative reforms. Utilizing a normative juridical approach, this study compares legal texts and analyzes court decisions to map the tensions between substantive recognition and legal formalism. The findings reveal that the jurisprudence of the Supreme Court is ambivalent: progressive in adat family law, yet highly formalistic in land disputes, where state-issued formal titles consistently override the historical claims of indigenous communities. Meanwhile, the legislative shift to the